PERMAINAN CATUR INGGRIS BERBASIS ANDROID MENGGUNAKAN ALGORITMA MINIMAX - Pratama, Deni Fajar; Tamatjita, Elizabeth Nurmiyati; Nugraheny, Dwi (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2016)
Today development of computer technology is growing rapidly, especialy in term of the game are certainly not stranger for the fans, from children to adults. The game has a positive impact that could indirectly hone the ability o f the brain and improve memory and patience. Catur Inggris is a strategy game like chess origin from Pekanbaru city, Riau province is generally played by two people, but more simple. Catur Inggris is based on Android with the programming C # language. Catur Inggris using Minimax algorithm with three difficulty levels that is, easy, medium, and hard. Minimax algorithm is an algorithm that using Depth-First Search method to find solutions step with limited depth. The results obtained from the test results using the algorithm method Minimax with Depth-First Search managed to generate possible winning position. Results obtained from tests using Minimax algorithm is 80% with five depth o f Depth-First Search tree four wins for the computer and a victory for the player, therefore Minimax algorithm can work well Catur Inggris game, and results test for user with 30 respondents get results 84%, therefore Catur Inggris game had a very good response from the users